Chiral tertiary propargylic alcohols via Pd-catalyzed carboxylative kinetic resolution. Issue 23 (28th October 2020) - Wang, Jie; Zhang, Wanli; Wu, Penglin; Huang, Chaofan; Zheng, Yangguangyan; Zheng, Wei-Feng; Qian, Hui; Ma, Shengming
Abstract : A highly efficient Pd/H + -cocatalyzed kinetic resolution reaction of tertiary propargylic alcohols has been reported. Abstract : A highly efficient Pd/H + -cocatalyzed kinetic resolution reaction of tertiary propargylic alcohols has been reported. The method provides an efficient approach to prepare a series of propargylic alcohols bearing a chiral quaternary stereocenter in good yields and remarkable enantioselectivities (93–>99% ee) under mild and operationally simple reaction conditions tolerating a broad range of functional groups. The practicality of this method has been demonstrated via the 4-gram-scale synthesis of chiral propargylic alcohol ( S )-1a .